JUMLAH SEL TROFOBLAS YANG MENGALAMI APOPTOSIS PADA PRE EKLAMPSIA/EKLAMPSIA LEBIH TINGGI DIBANDINGKAN KEHAMILAN NORMAL - Keman, Kusnarman; Prasetyorini, Nugrahanti; Langgar, Madeline J. (Fakultas Kedokteran Universitas Brawijaya, 2008)
Hypoxia exposed trophoblast cells will cause apoptotic process, that correlate with up-regulation of p53 and Bax protein expression; and down-regulation of anti-apoptotic Bcl-2 protein. Apoptotic process and up-regulation of p52, and down-regulation of anti-apoptotic Bcl-2; also find both on trophoblastic samplefrom preeclampsia/ eclampsia complicated pregnancy, and normal pregnancy. The aim of this study is, to prove that the amount of apoptotic trophoblast cells on trophoblast tissue sample from preeclampsia/ ecclampsia complicated pregnancy, were higher then those of normal pregnancy. This research was laboratory cross sectional study, that observed immunohystochemically, p53 and BCl-2 protein expression; also the DNA-fragmented technically (TUNEL) to detect apoptotic cells on trophoblastic samples from preeclampsia/ eclampsia complicated pregnancy, compare by the normal pregnancy. On this study, we found that the amount of trophoblast cells that expressed of p53 protein (22.70 ± 2.90), were higher then those of normal pregnancy. (8.2 ± 4.99). The different was statistically significant. (t test; p ≤0.000). We also found that an apoptotic process on trophoblast cells of preeclampsia/ eclampsia placenta (15.3 ± 3,56) were higher then those of normal pregnancy (4.7 ± 1.89). The different was statistically significant. (t test; p ≤0.000).